Using Geospatial Analysis to Determine Access Gaps Among Children with Special Healthcare Needs - Pamela DeGuzman; Paige Altrui; Aubrey L. Doede; Marcus Allen; Cornelia Deagle; Jessica Keim-Malpass; Jessica Keim-Malpass (Mary Ann Liebert, 2018)
Purpose: To examine geospatial gaps in identification and evaluation of children with special healthcare needs (CSHCN) within public child development centers (CDCs). Methods: A descriptive geospatial design was used to visually depict service gaps, proximity, and clustering of area-level sociodemographic attributes of Virginia counties, and patient-level data within each CDC. Results: Geospatial analysis shows population density of uninsured children against CDC resources. Data visualization facilitates policy advocacy based on the identification of care and screening gaps for CSHCN. Conclusion: This project illustrates the collaborative potential between researchers and Health Department members to identify gaps in access to care.